Optimisme dan Sabar dalam Al-Qur’an: Kunci Keteguhan Iman dan Harapan - Ananda Dhurrotul Waliyyah; Siti Zulaikha; Ana Rahmawati (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2024)
This article aims to explore the concepts of optimism and patience in the perspective of the Qur'an, as well as their role as keys to steadfastness and hope in the life of a Muslim. In the context of the Qur'an, optimism can also be understood as a positive attitude in facing life but also as a deep belief in facing life, but also as a deep belief in God's love and help that never breaks. On the other hand, patience, (sabr,) is a mental attitude that teaches someone to be steadfast and patient in facing life's tests, whether in the form of difficulties, suffering and challenges Elsewhere, this article analyzes a number of verses in the Qur'an that link these two concepts, such as in the letter Al Baqarah, (2; 153), which links sabr and prayer, as well as the letter Ash-sharh (94: 5-6) which illustrates that after difficulties there must be ease. This study also reviews how optimism and patience can form steadfastness (thabat) in facing all forms of tests, thus strengthening hope to achieve better life goals, both in in this world and in the hereafter. Apart from that, this article shows that optimism combined with patience can foster self-confidence, calm the soul, and encourage individuals to continue trying even when facing difficulties. Thus, both function as a source of spiritual strength that strengthens mental endurance and emotional, as well as maintaining life balance in living a life journey full of dynamics.